Owl be home for Christmas [large type] - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries., 2019)
"It's a few days before Christmas, and Meg's grandfather is hosting a scientific conference on owls at the Caerphilly Inn. Most of the family are there, helping out in one capacity or another, including Meg's grandmother, Cordelia--invited by Grandfather in rare gesture of peace-making, to share her expertise on rehabilitating large birds, including owls. An unexpectedly severe snow storm traps the conference-goers in the hotel, and one of the visiting ornithologists is murdered. Even if Caerphilly is able to clear the roads in time, Chief Burke doesn't want the various suspects to scatter to half a dozen continents before he identifies the killer, so there's a very real possibility that none of them will make it home for Christmas . . . at least not unless Meg comes to the rescue. Full of intrigue and snow, this Christmas mystery will take readers home to Caerphilly for Christmas"--Amazon.